DEVELOPMENT OF WEB-BASED MEDICAL RECORD INFORMATION SYSTEM AT PUSKESMAS SUWAWA - Sri Novita Bumulo (President University, 2023)
Abstract-This project addressesproblems and provides ideas and suggestions forproblems that occur at the Suwawa HealthCenter, because it is known that each HealthCenter has a medical record for each patient.After conducting research at the SuwawaCommunity Health Center, they experiencedproblems in managing medical records becausethey still used handwriting which might causemedical records to be scattered or possibly lost.will be required to maintain handwritten medicalrecords. For this reason, the creation of a web-based medical record information system willgreatly assist and facilitate health services inmanaging or storing patient medical records, itcan also make it easier to view the entire medicalrecord history of every patient who has beentreated at a Public Health Center. Apart fromthat the Suwawa Health Center does not yet haveaccess to information that is given to local peopleonline, therefore through this system it providesinformation for the community regardingservices and the time needed by the community toseek treatment at the Suwawa Health Center